2021
DOI: 10.3389/fcell.2021.678532
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Induced Inflammatory Cytokines in Osteoblasts: A Guided Path to Osteolysis in Bone Metastasis

Abstract: Bone metastasis (BM) is a dismal complication of cancer that frequently occurs in patients with advanced carcinomas and that often manifests as an osteolytic lesion. In bone, tumor cells promote an imbalance in bone remodeling via the release of growth factors that, directly or indirectly, stimulate osteoclast resorption activity. However, carcinoma cells are also characterized by an altered metabolism responsible for a decrease of extracellular pH, which, in turn, directly intensifies osteoclast bone erosion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 85 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…In a scenario wherein arthroplasties are progressively having operated on transplant patients, osteolysis is the major cause of errors during joint replacement prosthesis has received much interest [ 1 ]. Wear particle-induced osteolysis caused by ultra-high molecular weight polyethylene has been the practice through which reconstructive wreckage statically released from the substratum of prosthetic joint surfaces provokes an inflammatory system that favors bone catabolism, culminating in weakening of prosthetics and imminent downfall or cracking [ 2 , 3 ]. Wear particles made of ultra-high molecular weight polyethylene (UHMWPE) have now been identified as among the most common causes of aseptic loosening in total orthopedic implants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a scenario wherein arthroplasties are progressively having operated on transplant patients, osteolysis is the major cause of errors during joint replacement prosthesis has received much interest [ 1 ]. Wear particle-induced osteolysis caused by ultra-high molecular weight polyethylene has been the practice through which reconstructive wreckage statically released from the substratum of prosthetic joint surfaces provokes an inflammatory system that favors bone catabolism, culminating in weakening of prosthetics and imminent downfall or cracking [ 2 , 3 ]. Wear particles made of ultra-high molecular weight polyethylene (UHMWPE) have now been identified as among the most common causes of aseptic loosening in total orthopedic implants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[50]); carcinoma cells metastasizing to the bone share with bone sarcoma cells different mechanisms of proton extrusion, including the expression of V 1 B 2 and V 0 c V-ATPase subunits, CAIX, MCT1, and MCT4. As an example, we have recently found mRNA expression of CAIX in breast and renal carcinoma cell lines, with a significant increase under reduced oxygen conditions with respect to normoxia [50,56]. Additionally, different isoforms of V-ATPase, including the V 1 C 1 [57] and the V 1 B 2 and V 1 G 1 subunits [58], are expressed by breast carcinoma cells with a specific tropism for bone.…”
Section: Expression Of the Ion Extrudersmentioning
confidence: 98%
“…Other factors, such as interleukin 1 (IL-1), interleukin 6 (IL-6), tumour necrosis factor-alpha (TNFa), parathyroid hormone-related protein (PTHrP), or transforming growth factorbeta (TGFb), mediate RANKL receptor (RANK) expression on the surface of osteoclasts, thereby favouring osteoclast maturation and activation [59]. Furthermore, we have recently demonstrated that a low pH further induces osteoclast activity, both directly and indirectly, by stimulating osteoblasts to secrete pro-osteoclastogenic paracrine mediators such as IL-8 and IL-6 [56].…”
Section: Bone Resorption As a Source Of Extracellular Acidificationmentioning
confidence: 99%
“…Maruotti et al ( 5 ) revealed that osteoblast disorders play a crucial role in the pathogenesis of OA, stimulating the osteoblast-induced production of large transcription factor quantities, growth factors and other proteins involved in OA pathogenesis. In addition, Di Pompo et al ( 6 ) previously reported that osteoblasts promoted the secretion of osteoclastic cytokines and inflammatory mediators in an acidic environment (pH 6.8), further exacerbating OA.…”
Section: Introductionmentioning
confidence: 99%